Novel antibodies against RCD-8 as a tool to study processing bodies - Gudkova, D.O.; Panasyuk, G.G.; Nemazanyy, I.O.; Filonenko, V.V. (Вiopolymers and Cell, 2010)
Aim. To develop the model system for processing bodies (PBs) state monitoring and accomplish it in the future as a possible read-out of mTOR activity in mammalian cells. Methods. In course of this study we raised polyclonal antibodies against one of the PBs scaffold proteins – RCD-8 and employed cell imaging technique. Results. It has been shown that the obtained antibodies recognize the intracellular structures, namely PBs. The detected protein co-localized with known marker of PBs – DCP1a, and partly with marker of SGs – CPEB. Conclusions. Based on changes of PBs number and size in cells after exposure to known inductors or inhibitors of PB formation we prove the specificity of generated antibodies and possibility of their application for studies on the processing bodies dynamics controlled by mTOR-dependent signaling.